2002
DOI: 10.1097/00130535-200209000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vest Therapy in Pediatric Long-Term Care

Abstract: VT resulted in more effective suctioning of pulmonary secretions, reduced incidence of pneumonia, and reduced number of hospitalizations for pneumonia. In patients with epilepsy, VT resulted in reduced seizure frequency. VT was tolerated well, without complications or side effects. Further clinical investigations of the use of VT in cerebral palsy are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Figure shows that 3,347 unique records were identified, from which 233 full texts were assessed for eligibility, and 37 records retained. Three studies were reported in two papers each (Plioplys, Ebel, & Kasnicka, ; Plioplys, Lewis, & Kasnicka, ), (Adams, ; Adams et al, ), (Sullivan et al, ; Sullivan et al, ), so each pair was merged, giving a total of 34 studies in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure shows that 3,347 unique records were identified, from which 233 full texts were assessed for eligibility, and 37 records retained. Three studies were reported in two papers each (Plioplys, Ebel, & Kasnicka, ; Plioplys, Lewis, & Kasnicka, ), (Adams, ; Adams et al, ), (Sullivan et al, ; Sullivan et al, ), so each pair was merged, giving a total of 34 studies in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The study designs were classified using the AACPDM rating systems shown in Table . There were three Level II studies (Lee et al, ; Siriwat et al, ; Yuan et al, ), two Level III studies (Hutzler et al, ; Shin & Kim, ), 25 Level IV studies (Adams, ; Adams et al, ; Bozkurt et al, ; Cheung et al, ; Faria et al, ; K. Fitzgerald et al, ; Garuti et al, ; Hartzell et al, ; Hsiao & Nixon, ; Ishimaru, ; Keskinen et al, ; Lephart & Kaplan, ; Littleton et al, ; Maher et al, ; Manrique & Sato, ; Meece et al, ; Miyazawa et al, ; Myatt & Beckenham, ; Noonan et al, ; O'Loughlin et al, ; Plioplys et al, ; Plioplys et al, ; Plioplys & Kasnicka, ; Preciado et al, ; Romero et al, ; Sullivan et al, ; Sullivan et al, ; Vijayasekaran et al, ), and four Level V studies (Cheng et al, ; Denbar, ; Kim et al, ; Worley et al, ). No studies were classified as Level I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, use of this modality has not been well studied in patients with NMD. In seven patients with quadriplegic cerebral palsy, routine use of HFCWO therapy resulted in a reduction in the number of pneumonias and respiratory-related hospitalizations in the year after introduction of the therapy compared with the year before [34]. The authors also reported improved effectiveness of suctioning with HFCWO use in those patients with tracheostomies.…”
Section: Mucus Mobilization Devicesmentioning
confidence: 91%